anonymous
  • anonymous
how do I Solve Systems of Equations by Elimination?!
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Can someone solve these equations by elimination word by word?! x+y=2 & 2x+3y=12
jdoe0001
  • jdoe0001
\(\large \begin{array}{llll} x&+y&=&2\\ 2x&+3y&=&12\\ \hline\\ \square?&\square?&&\square? \end{array}\) notice that, the top and bottom equations are adding each other there to get some result at the bottom now, what we want, is to get a 0 on say the "x column" so that, something added to the say "2x", will yield us 0, that is \(\large \begin{array}{llll}\square? \\ 2x\\ \hline\\ 0\end{array}\)
jdoe0001
  • jdoe0001
what "something" do you think we need to make that SUM to 0? that is "something" + 2x = 0 what should that "something" be?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
your equation x+y=2 and 2x+3y=12 now our aim is to make one term on equation equal to other so that we can cancel it , for that we will multiply first equation by 2\[2(x+y=2)\]\[2x+2y=4\] consider it as eq 3, now subtract eq 2 from 3 or vice versa \[(2x+2y=4)-(2x+3y=12)\]\[2x+2y-2x-3y=4-12\]\[-y=-4\]\[y=4\] now for x we will substitute ot in eq 1 or any eq you want \[x+4=2\]\[x=2-4\]\[x=-2, y=4\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.